The Class of Weakly Normal Operators - Shaakir, Laith K.; Abdulwahid, Elaf S.; Hijab, Anas A. (Iraqi Journal of Science, 2023)
Our purpose in this paper is to introduce new operators on Hilbert space which is called weakly normal operators. Some basic properties of these operators are studied in this research. In general, weakly normal operators need not be normal operator, -normal operators and quasi-normal operators.